Arbuscular Mycorrhizal Symbiosis Primes Tolerance to Cucumber Mosaic Virus in Tomato - Miozzi, Laura (Viruses, 2020)
Tomato plants can establish symbiotic interactions with arbuscular mycorrhizal fungi (AMF) able to promote plant nutrition and prime systemic plant defenses against pathogens attack; the mechanism involved is known as mycorrhiza-induced resistance (MIR). However, studies on the effect of AMF on viral infection, still limited and not conclusive, indicate that AMF colonization may have a detrimental effect on plant defenses against viruses, so that the term “mycorrhiza-induced susceptibility” (MIS) has been proposed for these cases. To expand the case studies to a not yet tested viral family, that is, Bromoviridae, we investigated the effect of the colonization by the AMF Funneliformis mosseae on cucumber mosaic virus (CMV) infection in tomato by phenotypic, physiological, biochemical, and transcriptional analyses. Our results showed that the establishment of a functional AM symbiosis is able to limit symptoms development. Physiological and transcriptomic data highlighted that AMF mitigates the drastic downregulation of photosynthesis-related genes and the reduction of photosynthetic CO(2) assimilation rate caused by CMV infection. In parallel, an increase of salicylic acid level and a modulation of reactive oxygen species (ROS)-related genes, toward a limitation of ROS accumulation, was specifically observed in CMV-infected mycorrhizal plants. Overall, our data indicate that the AM symbiosis influences the development of CMV infection in tomato plants and exerts a priming effect able to enhance tolerance to viral infection.